Direct Oral Anticoagulants in Patients with Atrial Fibrillation and Renal Dysfunction - Z. D. Kobalava; A. A. Shavarov; M. V. Vatsik-Gorodetskaya (Рациональная фармакотерапия в кардиологии, 2021)
Atrial fibrillation and renal dysfunction often coexist, each disorder may predispose to the other and contribute to worsening prognosis. Both atrial fibrillation and chronic kidney disease are associated with increased risk of stroke and thromboembolic complications. Oral anticoagulation for stroke prevention is therefore recommended in patients with atrial fibrillation and decreased renal function. Each direct oral anticoagulant has unique pharmacologic properties of which clinician should be aware to optimally manage patients. The doses of direct oral anticoagulants require adjustment for renal function. There is debate regarding which equation, the Chronic Kidney Disease Epidemiology (CKD-EPI) equation vs. the Cockcroft-Gault equation, should be used to estimate glomerular filtration rate in patients with atrial fibrillation treated with direct oral anticoagulants. Our review tries to find arguments for benefit of direct oral anticoagulants in patients with renal dysfunction.